Guía de Aves del Cantón Saquisilí - Aimacaña Lema, Byron Paúl (2019)
The present research is based on the monitoring of avifauna species with the purpose of realize a bird guide of the Saquisili Town secondary information; where it was analyzed the current situation of the area study, resulting the monitoring would perform in the three zones located inside Cochapamba and Chantilin countryside, because these places are surrounded by natural affluence, in which It allows the reproduction and abundance of avifauna species, in the monitoring were applied two methodologies; the intensive search method and the census method through linear transect techniques and point counting, in which these are very used in biodiversity inventories and avifauna inventories, the two methods used the intensive search method are applied in the two lakes (Laguna de Patos and Laguna de Tiloncoha) through strategic points of direct observation in which resulted in 23 species being the Laguna de Patos is located in the Chantili Parroquial it has the most number of species, between the Passeriform Order and the Apodiform Order, in which the Anatidae the Yellow-billed Anad (Anas Georgia) Family has the most abundance; the census methodology was applied in the courses go and go back in each attraction, but because of the intervention of the surroundings of each area, it was not possible to monitor more avifaunistic species, resulting only 7 species of the total, at the end of inventory and analysis on the data collection in the field trips it gives as results, inside the town there are 30 avifaunistic species in which 26 are residents and 4 migratories, one hundred percent of the located species find according to the state of conservation (least concern) it means, those are not threat of disappearing in the near future. Finally, as a benefit of the project, deliver a bird guide, so that can be to take advantage of as a guide that allows communities and the surrounding area to know avifaunistic affluence nature of this town, therefore give the first step in the development of ecotourism, allow activities such as bird watching, promoting the move of tourists to the inside of the areas provide economic benefits that allow the conservation of the attractions and the sustainable development of the town and the province.